PERAN MASYARAKAT DAN PEMERINTAH DALAM PENANGGULANGAN BENCANA BANJIR DI KECAMATAN KOTA TANGAH KOTA PADANG - Aulia Putri, Novi; Juita, Erna; Juita, Nefilinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to find out and analyze, (1) The role of the community in managing flood disasters in Koto Tangah District, Padang City, (2) The role of the government in managing flood disasters in Koto Tangah District, Padang City, (3) The effectiveness of the role of the community and government in managing flood disasters in Koto Tangah District, Padang City. The methods used are quantitative and qualitative with field observation, interviews, questionnaires and documentation approaches. The research results show that the community's role in flood disaster management is in the good category, carried out through involvement in mutual cooperation activities, community preparedness and participation in government programs. Meanwhile, the government's role is in the quite good category, through providing flood management infrastructure, disaster outreach, and distributing aid when floods occur.